Stolen sperm : should the law absolve an involuntary father from the duty to furnish child maintenance? - Smith, Samantha (Department of Private Law, 2015)
The terrain of family law is increasingly complex and diverse and is constantly adapting to the changing social, cultural, political and economic landscape in which it is located. It is thus open to much development, particularly in the area of parenthood. In its simplest form, parenthood results when two consenting adults, knowingly and willingly, engage in sexual intercourse to conceive a child. The allocation of parental rights and responsibilities is therefore simplified on the basis that both parties consented to becoming parents. However, the assignment of legal parenthood is not always as clear-cut. Over the past three decades, the courts in the United States, in particular, have been tasked with adjudicating cases in which a biological father has refused to furnish child maintenance on the grounds that he was sexually forced into parenthood. These claims have highlighted the tension between biological fatherhood and legal parenthood, and have thus created a legal, ethical and practical quagmire in family law. Therefore this dissertation will explore the instances in which paternity is deceitfully imposed, the plethora of legal problems that arise and the possible legal routes open to involuntary fathers to avoid paying child support.